Analisis Kebijakan Pendidikan dan Pengaruhnya terhadap Sistem Sekolah Modern - Chici Cahyaningrum; Nafisha Arifa Azahra; Wahyu Musrifah Ramadani; M.Hasbiyalloh Ghoutsul Bourdan; Ivo Sindia Nur Azizah (Al-Kindi, 2026)
Educational policy in Indonesia continuously evolves to address contemporary challenges and eliminate the discriminatory legacy of the colonial era. This study aims to analyze the historical development of educational policies in Indonesia and their influence on the modern school system, specifically regarding curriculum, quality standardization, decentralization, and funding. The method employed is qualitative through library research, with secondary data analyzed using content analysis techniques. The results indicate that the dualistic system of the colonial period triggered a structural transformation within traditional Islamic education, making it more adaptive. In the modern era, this transformation culminates in the implementation of Kurikulum Merdeka, which focuses on student-centered learning, and the transition of evaluation from the National Examination to the Computer-Based National Assessment (ANBK). Furthermore, decentralization policies initiated by Law No. 22 of 1999 and the optimization of funding through the School Operational Assistance (BOS) funds have proven to grant greater autonomy to regions and schools. However, challenges such as disparities in technological infrastructure, limited competence of educators, and inequalities in financial management between urban and rural areas remain major obstacles to achieving an equitable and inclusive educational ecosystem.